Storytelling Cultural Hybridity: A Narrative Study of Southeast Asian Representation in Raya and the Last Dragon - Aulia Afniar Rahmawati; Jokhanan Kristiyono; Athok Murtadlo; Mochammad Arkansyah; Supriadi (Jurnal Spektrum Komunikasi, 2025)
The research analyzes cultural hybridity in Southeast Asian animated storytelling through an assessment of Raya and the Last Dragon film. Structural narrative analysis and visual semiotics techniques are used to evaluate how the film delivers Southeast Asian identity perspectives to non-regional audiences. The analysis of the movie employs Claude Lévi-Strauss’s binary opposition framework to reveal cultural tensions between trust and betrayal and unity and fragmentation which repeatedly appear in the text. The film's visual design combines various Southeast Asian cultural elements into an original unified imagery which includes architectural designs and weapons and magical creatures alongside costume styles. Rather than offering a descriptive reading of narrative alone, this study decodes how hybrid representations shape ideological messages. This study contributes to global media representation studies via analysis that back up accurate representation of culture with observation both of precise and truthful material, as well as within viewing audience. This paper uses narrative theory and visual cultural analysis for studying transnational animation as it presents cultural pride and ideology through interdisciplinary methodologies.